Blue Economy : Kesimbangan Perspektif Ekonomi dan Lingkungan - Ilma, Ajeng Faizah Nijma (Jurnal Ilmu Ekonomi dan Pembangunan, 2014)
Blue economy is a process in which all the following raw materials derived from natural production process and follow the way nature works. Economic models of the future will take into account the advantages and strategy of innovation by following the natural conditions. Blue Economy is a tool that can be used to improve the unfavorable economic conditions and create more activity in the form of a sustainable model. Providing the best solution by transferring the economy and result in the community for the future so that it will be better. Indonesian nation has been indoctrinated to become the nation's agricultural and economic use of the land base oriented as its economic growth pattern. However, the strength of the domestic market consumption value indicates that there should be digging back potential economic growth potential there to be able to be a formidable nation. The contribution of fisheries and marine sector experienced an increasing trend. However, the welfare of the people residing in coastal areas is still very low, lower than the society that focuses on development in other sectors.Keywords: blue economy, marine sector, economic growth